Analisis Kualitas Pelayanan terhadap Kepuasan Pasien Rawat Jalan di Puskesmas Puuwatu Kota Kendari menggunakan Metode SERVQUAL - Adryan Fristiohady; La Ode Muhammad Fitrawan; Yusniati Dwi Pemudi; Sunandar Ihsan; Ruslin Ruslin; Mentarry Bafadal; Nurwati Nurwati; Ruslan Ruslan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The quality of outpatient services can be measured by the SERVQUAL model that takes into account 5 dimensions, namely tangible, reliability, responsiveness, assurance, and empathy. The purpose of this study was to look at the effect of service quality on outpatient satisfaction at the Apotek Puskesmas Puuwatu Kota Kendari. The subjects in this study were 34 outpatients. The analysis technique used is gap analysis to compare expectations and reality received by patients, normality test data based on questionnaire patient satisfaction that has been tested for validation. The results of this study indicate the average value of the gap in the pharmacy of Apotek Puskesmas Puuwatu Kota Kendari amounting to 0.27. From the value of the gap, the lowest gap value in the pharmacy center of Puuwatu is the place of service, and the provision of inadequate drug information of -0.24. Based on the paired t-test where significant value> 0.05 then Ho is rejected and Ha accepted so that means a significant difference between the quality of service to the satisfaction of patients in Apotek Puskesmas Puuwatu Kota Kendari. This study concludes that there is a significant gap between expectations and reality at the Apotek Puskesmas Puuwatu Kendari City